We live like Khayalat (scarecrows): An ethnography of a Palestinian village in Egypt - Abdrabo, Amal Adel (AUC Knowledge Fountain, 2016)
Based on my preliminary research on the literature, I can argue that this is the first ethnographic study of the social life of the village of Jazirat Fadil and its inhabitants. Jazirat Fadil is a Palestinian village of about 5,000 people who have lived in Egypt since 1948. The village is precisely located in Al-Sharqiya province about 150 kilometers (93 miles) east of Cairo. The village has hosted scattered Palestinian refugees who fled their home village of Beersheba (Byr Sab' / Ba'ar Sab') after the 1948 exodus. There are no official records of the number of inhabitants in the village with the exception of insignificant information in newspaper articles and a brief mention in a previous ethnographic study about exiled Palestinians in Egypt . The current fieldwork depended on participatory observation, oral history testimonies and field notes, while taking advantage of the shared language between us, Arabic. I also decided to live in the community to be studied for a while to help counter the difficulty of access. During my three-month study I was able to observe how they perform their day to day life in the village. In this sense, this research project attempts to determine how the inhabitants of Jazirat Fadil, as agents, managed to navigate, negotiate, and contest the social context they have been forced into after their exile from Palestine since 1948. Based on that, the research concentrates on how the storytellers who are involved in this research, my interlocutors and myself, managed the performance of both being and doing while living in the village of Jazirat Fadil. The core idea is about the ghostly/shadowy existence of the people of this community and how they managed to penetrate what was forced upon them by their active agency and their cultural heritage of survival. In other words, this project is about the dialectical discourse between being and doing as seen in the daily life of my interlocutors and myself. The field experience conveyed three different dimensions of this process of negotiation across past, present, and future times that are overlapping synchronically. For the purpose of mapping my co-storytellers’ steps until their settlement at Jazirat Fadil, the first section is entitled the (up)rooted and is related to their past history and where they come from. The present has its own dimensions that are related to their past memory and to the actual process of agency as they try to survive: how they managed to overcome being (un)seen within their new context as well as being (un)certain about their memory, as is the case of the old timers of Jazirat Fadil. Finally, when it comes to the future of an exiled community living in the midst of Egyptian society and suffering from uncertainty and lack of recognition by the international humanitarian aid organizations , the question will be whether the community of Jazirat Fadil holds some sort of hope regarding their future or if it is too (un)imaginable for them to bear hope. The constellation of chapters that compose the body of this thesis are not written for the purpose of proving a certain argument. They do not proceed toward a certain point, but rather try to capture different moments within the social life of the village of Jazirat Fadil that I witnessed during my stay there. These moments are “juxtaposed in mutual discordance so as to echo the discordance of the phenomena being studied,” (Daniel 1996:6). This being said, the story that is narrated through the chapters of this thesis is not only about my interlocutors, but it is also about me as an outsider who went to the field with certain assumptions and was altered through the experience.